2022
DOI: 10.1371/journal.pone.0276137
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of soil-transmitted helminths infection among individuals in model and non-model households, South West Ethiopia: A comparative cross-sectional community based study

Abstract: Soil-transmitted helminths (STH) is a term used to refer to infections caused by intestinal worms mainly due to A. lumbricoides, T. trichiura, and hookworm species which are transmitted through contaminated soil. This study was conducted to assess the prevalence and intensity of STHs infection among individual members living within the selected household heads (HHs) certified either as a model HHs or non-model HHs based on the implementation level of a training program known as the Health Extension Program (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…This concurs with findings from similar studies conducted in Nigeria [12, 26–27, 31]. Using water cisterns and pit toilets at home was significantly associated with higher odds of infection, which contradicts the findings of other studies [28, 40, 4648]. The higher infection odds observed for adolescents who use water cistern is not surprising since the majority of the adolescents who tested positive for STH infections do not wash their hands after defecation.…”
Section: Discussionsupporting
confidence: 78%
“…This concurs with findings from similar studies conducted in Nigeria [12, 26–27, 31]. Using water cisterns and pit toilets at home was significantly associated with higher odds of infection, which contradicts the findings of other studies [28, 40, 4648]. The higher infection odds observed for adolescents who use water cistern is not surprising since the majority of the adolescents who tested positive for STH infections do not wash their hands after defecation.…”
Section: Discussionsupporting
confidence: 78%
“…The inadequacy of knowledge among the SAC has been substantiated by evidence from several studies in Africa for instance studies done in Malawi, Kenya, Uganda, and Tanzania (16-20). Poor environmental and sanitary conditions are linked to SCH infections (21) while STH is transmitted through contaminated soil (22, 23). Our findings revealed that most participants associated these diseases with drinking dirty contaminated water (17).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts displayed by each governing body in maintaining and keeping up-to-date open-access databases or infrastructure and technical outreach organizations are to ensure that every country would have the latest disease intelligence and technical skills in order for effective surveillance, preventive, and disease management control to be executed according to each country's governing leadership. Importance of having centralized data sharing at a regional scale has been highlighted in a study by Alemu et al (2022). With access to publicly available standardized survey and treatment coverage data, which was at first unavailable probably due to absence of reports by the country's Ministry of Health to the WHO, they were now able to access ample amounts of collected evidence pointing to the advantages of school-based deworming programs and LF MDA campaigns.…”
Section: Comparisons With ML Application In Cancer Research Computer ...mentioning
confidence: 99%
“…Hence, molecular-based assays such as PCR, real-time PCR and digital PCR, loop-mediated isothermal amplification (LAMP), and cell-free DNA detection provide a more sensitive, less labor-intensive, and high-throughput detection method despite incurring additional costs for detection and surveillance programmes(Becker et al 2018;Manuel, Ramanujam & Ajjampur 2021).Measures taken in managing cases of STHs are shared among other helminth infections. Implementing MDA programs targeting high-risk groups in endemic tropical and subtropical areas has been recognized to be effective in eliminating STH globally(Alemu et al 2022). In underdeveloped areas with poor facilities but endemic with STHs, adopting the principles of WASH by providing adequate sanitation, improving waste management facilities, plus public education on hygiene practices and behavioral changes targeted to populations at risk would accelerate the elimination goal(Sato et al 2019).…”
mentioning
confidence: 99%